Intensitas penggunaan gadget dan obesitas anak prasekolah di Kota Yogyakarta - Fajar Sri Tanjung; Emy Huriyati; Djauhar Ismail (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Intensity of gadget use among overweighed preschool children in YogyakartaPurposeThe purpose of this paper was to determine the relationship of the gadgets uses intensity among obesity preschool children in Yogyakarta.MethodsThis cross-sectional study was conducted involving all preschool children in playgroup and kindergarten in Yogyakarta who did not attend the full day school program.ResultsPreschool children with high-intensity use of gadgets are 1.3 times more likely to be obese (p= 0.028, RP = 1.25). Preschool children with high-intensity use of gadgets, high education father, high sedentary behavior, adequate social economy, and poor diet are 2.1 times more likely to be obese.ConclusionThe incidence of obesity in preschool children is more common among children with high-intensity use of gadgets.